AN ANALYSIS OF EFL AUTONOMOUS LEARNERS IN LEARNING ENGLISH - ERICA FAJAR INDAH; DINA RACHMAWATI; SUTRIS SADJI EVENDDY (LINGUISTICA, 2021)
This research aimed to find out the factors affecting the autonomous learners in learning English and how these factors can influence the autonomous learners in learning English. This research employed qualitative narrative research. Narrative research was deemed to be relevant for this research since it deals with the specific phenomenon of the autonomous learner which analyzed life experience from the participants in learning English. The research subjects were two identified of autonomous learners. The data was taken by conducted interviews. In analyzing the data, the researcher used some procedures; data condensation, data display, and drawing conclusion/verification. The research revealed a finding related to the research question indicating that (1) internal and external factors were the factors affecting autonomous learners in learning English. From internal factors, it was argued that self- motivation (passion and willingness) was the biggest factor effecting autonomous learners eager to learn English. In addition, they also mentioned several external factors such as the family environment, school environment, and teachers as other factors that affected them in learning English (2) from several factors affecting autonomous learners in learning English, the participants also explained how these factors could encourage them in learning English, because of there were self-initiation, self-direction, and self-realization in themselves that stimulate them to become autonomous in learning. From these findings, it can be inferred that teachers or lecturers could play a role to promote students learning autonomy in order to stimulate students’ others positive psychological behavior, English proficiency and academic achievement.